2020
DOI: 10.21608/sinjas.2020.86376
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF CHEMICAL NITROGEN FERTILIZER LEVEL AND HUMIC ACID RATE ON Gladiolus grandiflorus PRODUCTIVITY

Abstract: during two successive seasons 2017-2018 and 2018-2019 to study the effect of various levels of nitrogen fertilizer (0, 100, 200 and 300 kg fed -1 ) in combination with different rates of humic acid (0, 150, 250 and 350 ppm) as a foliar spray on plant growth, flowering characteristics, corms and cormels characteristics and chemical constituents. The obtained results cleared that using 200 kg fed -1 nitrogen in urea forms with 350 mgl -1 humic acid as a foliar spray gave the maximum value in each of vegetative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Foliar fertilization was more effective and significantly enhanced the shoot and flower stem growth compared to the control plants. Similar to our study, some researchers reported that foliar fertilization promoted the flower stem growth to the maximum levels in gladioli, which could have a constructive role in the development of the flowers [ 15 , 19 , 20 ]. Similar findings have been described where the administration of foliar fertilization treatments influenced the Calendula inflorescence yield, but not the chlorophyll parameters, where no significant differences were observed between the treatments [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Foliar fertilization was more effective and significantly enhanced the shoot and flower stem growth compared to the control plants. Similar to our study, some researchers reported that foliar fertilization promoted the flower stem growth to the maximum levels in gladioli, which could have a constructive role in the development of the flowers [ 15 , 19 , 20 ]. Similar findings have been described where the administration of foliar fertilization treatments influenced the Calendula inflorescence yield, but not the chlorophyll parameters, where no significant differences were observed between the treatments [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 91%